Cote D'Ivoire : Request for an Extended Arrangement Under the Extended Fund Facility and an Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Cote D'Ivoire. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses Cote D'Ivoire's Requests for an Extended Arrangement Under the Extended Fund Facility (EFF) and an Arrangement Under the Extended Credit Facility (ECF). Extending the gains of 2015, solid economic and fiscal performance continued in 2016. Strong investment and private consumption contributed to real GDP growth estimated at about 9 percent in 2015. In 2016, booming extractive industries and rising domestic demand supported activity in the commercial sector, which should sustain GDP growth at about 8 percent. The macroeconomic outlook remains favorable, but structural bottlenecks pose challenges to sustained strong growth. The IMF staff supports the authorities' request for the ECF and EFF arrangements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet